Synthesis and reactivity of azole-based iodazinium salts - Kuczmera, Thomas J.; Dietz, Annalena; Boelke, Andreas; Nachtsheim, Boris J. (Beilstein Journal of Organic Chemistry, 2023)
A systematic investigation of imidazo- and pyrazoloiodazinium salts is presented. Besides a robust synthetic protocol that allowed us to synthesize these novel cyclic iodonium salts in their mono- and dicationic forms, we gained in-depth structural information through single-crystal analysis and demonstrated the ring opening of the heterocycle-bridged iodonium species. For an exclusive set of dicationic imidazoiodaziniums, we show highly delicate post-oxidation functionalizations retaining the hypervalent iodine center.
Keywords: building block; heterocycles; hypervalent compounds; iodonium salts; one-pot synthesis